2019
DOI: 10.1080/13645706.2019.1638411
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of eoSim – a low-cost and portable laparoscopic simulator

Abstract: Construct validity of eoSim -a low-cost and portable laparoscopic simulatorPurpose: To examine the construct validity of the low-cost, portable laparoscopic simulator eoSim using motion analysis.Methods: Novice and experienced surgeons (≤ 100 and > 100 laparoscopic procedures performed, respectively) completed four tasks on the eoSim using the SurgTrac software: intracorporeal suture and tie, tube ligation, peg capping and precision cutting. The following metrics were recorded: Time to complete task, distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In this study the continuous training group practiced once every two weeks. This was based on previous research regarding interval training and on a study by Gallagher et al who found that surgical skills decline after two weeks of non-use [ 16 , 31 ]. However, the optimal intersession interval (time between two independent training sessions) for continuous training remains unknown, particularly for the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the continuous training group practiced once every two weeks. This was based on previous research regarding interval training and on a study by Gallagher et al who found that surgical skills decline after two weeks of non-use [ 16 , 31 ]. However, the optimal intersession interval (time between two independent training sessions) for continuous training remains unknown, particularly for the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the suturing task during test sessions was assessed by the parameters distance and time of the SurgTrac software. Previous studies have shown evident construct validity in the parameters time and distance [ 14 , 16 ] therefore, these are included as primary outcome parameters in this study. The LS-CAT form is used, additionally to the SurgTrac parameters, to provide an objective assessment on the quality of the suture, which is not possible by only measuring time and distance traveled by the instruments.…”
Section: Methodsmentioning
confidence: 99%
“…Our current challenge is to accommodate the model for online learning of technical skills, incorporating simulators to the resource portfolio in a new version of the MISTELA platform. Simulators are currently used to train technical skills at basic and intermediate levels and can be effective in the diagnosis of surgical skills [25,26]. Their use will typically involve deliberate, repetitive practice drills to achieve progressive automation of accurate movement patterns [27].…”
Section: Discussionmentioning
confidence: 99%
“…1 a Precise peg transfer task. b Suturing task performed on the LaparoscopyBoxx take-home simulator [16,22] 17 mm 3/8 curved needle) and performing an intracorporeal surgical knot (Fig. 1b), without a time limit.…”
Section: Tasksmentioning
confidence: 99%
“…The performance of the suturing task during the test sessions was assessed by the parameters of the SurgTrac software. Increase in skill level (primary outcome) was measured by the total time needed and distance traveled by the instrument tips, because previous studies have shown evident construct validity for these two parameters [21,22]. Furthermore, the LS-CAT was used for self-assessment and expert-assessment to provide an objective assessment of the quality of the suture and the knot (secondary outcome).…”
Section: Outcome Parametersmentioning
confidence: 99%